Effects of framing and knowledge on purchase intention of climate-friendly products—an experimental study on peat-free vs. peat-based potting soil - Mira Lehberger; Anne-Katrin Kleih; Kai Sparke (Agricultural and Food Economics)
Abstract The negative sustainability impact of peat use in the horticultural sector has recently come into political focus. A bottom-up approach would be to convince consumers to buy peat alternatives. This is where this study comes in. We examined the reactions of consumers (n = 1113) to differently framed potting soil messages. By including a no-intervention benchmark, we identify the magnitude of change in purchase intention resulting from framing interventions. We also apply measures to mitigate experimenter demand effect and social desirability bias. We find that in the absence of information, consumers prefer peat-based to peat-free potting soil. However, purchase intentions can be easily influenced in a more pro-environmental direction by providing additional information on soil type and framing messages on the environmental consequences of different soil types (peat-free vs. peat-based). We find evidence that higher levels of subjective knowledge are associated with lower intentions to buy peat-free potting soil, while higher levels of objective knowledge are associated with higher intentions. Our results highlight the importance of providing the right kind of information to encourage climate-friendly consumption, but also the relevance of consumer knowledge. We provide measures that different actors in the value chain can adapt to increase climate-friendly consumption.